2017
DOI: 10.1093/cid/cix005
|View full text |Cite
|
Sign up to set email alerts
|

Management of Ventriculoperitoneal Shunt Infections in Adults: Analysis of Risk Factors Associated With Treatment Failure

Abstract: This is the largest series of VP shunt infections in adults reported to date. VP shunt removal, particularly TSSR when the patient is shunt dependent, remains the optimal choice of treatment and does not increase morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 18 publications
0
49
1
Order By: Relevance
“…However, this is the exception rather than the rule. In a retrospective study of ventriculoperitoneal shunt infections of various aetiologies, the highest cure rates were observed for shunt replacement in a two-step procedure (shunt removaldshunt-free period with antibiotic treatment ± external drainagednew shunt implantation) in an unadjusted analysis [75]. In a decision-analysis model based on literature review, removal of all the components of the device and placement of a temporary EVD, combined with antimicrobial therapy, was the best treatment strategy in general, with an 85% cure rate [76].…”
Section: Management Of Implants and Shunts In Patients With Pnmmentioning
confidence: 99%
“…However, this is the exception rather than the rule. In a retrospective study of ventriculoperitoneal shunt infections of various aetiologies, the highest cure rates were observed for shunt replacement in a two-step procedure (shunt removaldshunt-free period with antibiotic treatment ± external drainagednew shunt implantation) in an unadjusted analysis [75]. In a decision-analysis model based on literature review, removal of all the components of the device and placement of a temporary EVD, combined with antimicrobial therapy, was the best treatment strategy in general, with an 85% cure rate [76].…”
Section: Management Of Implants and Shunts In Patients With Pnmmentioning
confidence: 99%
“…In 1 pediatric study, removal of the CSF shunt led to successful treatment in 90–100% of cases while treatment without shunt removal led to a 30% cure [5]. Pelegrin et al [6] reported that complete shunt removal followed by a shunt-free period plus antibiotic treatment led to an 89% cure rate in adult patients with CSF shunt infections. In 3 of our patients, the externalized peritoneal VP shunt catheter was used as a drain with successful shunt exchange performed once CSF cultures were negative (median 10 days).…”
Section: Discussionmentioning
confidence: 99%
“…In 3 of our patients, the externalized peritoneal VP shunt catheter was used as a drain with successful shunt exchange performed once CSF cultures were negative (median 10 days). Using a similar approach, Pelegrín et al [6] reported a 31% success rate in adult patients. Although our number of patients is small, this difference may be due to the infecting pathogens as the aforementioned study included infections caused by S. aureus (15%) and gram-negative bacteria (14%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little/no evidence for routine use of intraventricular therapy, and it is reserved for resistant cases. 29,30 Removal of the shunt is paramount: one study showed a treatment response of 95% for antibiotics and indwelling shunt removal, compared with 35% for antibiotics alone. 31 A new shunt may be placed as soon as 3 days after removal of the infected shunt and negative CSF cultures in the case of coagulase-negative staphylococcus or P. acnes infection, or 10 days after negative CSF cultures for S. aureus or Gram-negative bacilli.…”
Section: Shunt Infectionsmentioning
confidence: 99%